Consumer Protection in E-Commerce Business Agreements: A Study of Indonesian Positive Law - Hotman Manullang; Dahlan Dahlan; Henry Aspan (Utan Kayu Publishing, 2025)
Advances in information and communication technology have driven the development of e-commerce as a modern form of electronic-based business transactions. While online commerce offers convenience and efficiency, it also poses various risks for consumers, such as fraud, product nonconformity, and misuse of personal data. This situation places consumers in a weak position in their legal relationship with businesses, necessitating strong and effective legal protection. This study aims to analyze consumer protection regulations in e-commerce transactions based on Indonesian positive law and to examine the implementation of the principles of good faith and balance of interests as stipulated in Law Number 8 of 1999 concerning Consumer Protection. The research method used is normative legal research with statutory, conceptual, and literature study approaches. The results show that Indonesian positive law, through the Consumer Protection Law (UUPK), the Electronic Information and Transactions Law (UU ITE), Government Regulation Number 80 of 2019, and the Civil Code, has provided a normative foundation for consumer protection in electronic transactions. However, its implementation still faces obstacles such as weak supervision, difficulties in verifying the identity of business actors, and the suboptimal functioning of consumer dispute resolution institutions. The principles of good faith and balance of interests have also not been fully implemented due to the dominance of business actors in standard agreements, which tend to be detrimental to consumers.